(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
Girths of human body are significant parameters in pattern design, affecting the fitting and aesthetics of clothing. In this paper, 110 female undergraduates in Soochow University were measured by using photogrammetric measurement and 3D non-contact measurement system. The silhouette of human body was extracted by using software Matlab to obtain width and thickness. The measurements of the girths were gotten via software Imageware based on 3D point cloud data. According to the ratio between thickness and width, classification of those females was carried out and the regression equation of each cluster was obtained. The analyzed results show that the proposed non-contact measurement method can reduce influence of subjective factors. Regression equations can be applied to predict main girths. It will be helpful in the automatic design of garment pattern.